Parasitological assessment of selected vegetables and fruits sold at Tacloban City public market in March 2022 - Maglana, Meliscent Bles A. (2022)
Vegetables and fruits are essential parts of a healthy diet. However, several assessments and investigations reported parasitic contaminations in vegetables and fruits. This study aims to assess the presence of soil-transmitted helminths on selected vegetables and fruits sold at Tacloban City public market. In March 2022, a total of 30 samples (250g each) were collected. The samples were processed by means of sedimentation techniques and were examined using microscopy. Results showed that 15 out of 30 samples (50%) were contaminated with helminth ova/larvae. Among the vegetable samples, 11 samples out of 15 (73.3%) were found to be contaminated. Meanwhile, in fruit samples, 4 out of 15 samples (26.7%) were found to be contaminated. The number of contaminated samples among the selected vegetables and fruits are found to be not significantly different (p>0.050). The parasites found were Ascaris, Toxocara sp., and hookwork/free-living nematode larvae. Ascaris ova is the most frequent parasite, contaminating 14 out of the 30 total samples (46.7%), which also had the highest density of 140 ova/250 g in one ettuce sample (46.7%). Hookworm/freeliving nematode larvae are the least frequent parasite at 20%. These results show significant public health implications. Through these finds, the local health unit and regulatory authorities will be able to develop strategirs in preventing strategies in preventing and eliminating parasite contamination in vegetable and fruits.